Weather Anomaly Early Warning System on Koi Fishpond’s Water Quality Using Telegram Bot - Fiddin, Faril Aditya; Rasyid, Abdul; Waluyo, Waluyo (Jurnal Jaringan Telekomunikasi, 2024)
Koi fish farming is a popular practice in Blitar Regency. Larger ponds are required for cultivating Koi fish seeds, and it is common to use areas such as rice fields for these ponds. However, monitoring water quality in Koi ponds can be challenging, especially during unpredictable weather conditions. To address these difficulties, a study was conducted to develop an early warning system using the ESP32 DEVKIT V1 Module. The system provides real-time monitoring of Koi Pond water quality data through the Telegram app, using sensors to measure temperature, pH, and TDS levels. The data is then transmitted to the Telegram app for display. If the parameters differ from the standard values, the system triggers audio alerts, notifications, and a red LED indicator in the app. The test results show that the system performs well, with maximum recorded values of 31°C for temperature, 306 ppm for TDS, and a pH level of 9.4. The calibration errors for the system are measured at 0.37% for temperature, 0.77% for TDS, and 1.03% for pH. Overall, the system is effective in detecting poor water quality, offering automated alerts and manual control through the Telegram bot